„Kartoteka” w Grotesce – wyimek z twórczości Zofii i Władysława Jaremów - Eckert , Grzegorz (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2019)
Zofia and Władysław Jarema - the founders of the Groteska Theatre - from the beginning of their artitistic work in Krakow distanced themselves from perceiving the theatre of dolls as exclusively children-oriented. By gathering around themselves a group of distinguished artists, they consistently and reasonably built up the repertoire and Groteska stage for the adult audience. In their search, they included Konstanty Ildefons Gałczyński, Sławomir Mrożek, and Tadeusz Różewicz. This paper is an attempt at analysing and reconstructing the performance of Kartoteka (a drama by Różewicz), which was staged in Groteska Theatre (interpretation by Zofia Jarema, stage design by Kazimierz Mikulski) a few months after its Warsaw preview in the Drama Theatre. The author of the paper also discusses the type of influence which this performance and the Jaremas’ activity in general had on the contemporary theatre of dolls.